Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

Crip theory and the disabled identity: why disability politics needs impairment - Jenks, Andrew (Disability & Society, 2019)
This article highlights the importance of recognizing both the ontology of impairment as it relates to the creation of the disabled identity as well as why articulations of the disabled identity being ‘crip’ obfuscate potential politics. Examining how the disabled identity has been cast as a coherent social and political category, rather than the messy and complicated identity it truly is, I argue the adoption of a post-structuralist orientation by activists and advocates is bad for disability politics. Providing two examples, the first focusing on a publicized rape case of a person with an intellectual disability and the second on the importance of disability rights claims based on visibility of impairment, I show how articulations like those made in crip theory can have serious, negative implications for the lived experience of people with disabilities. I conclude with a call for disability studies scholars to engage disability politics in their work.
Keywords: 2000 à aujourd'hui; 2010-2019; activisme; approches et analyses; capacitisme; care; corps; cours; crip; discipline; droit; droit des personnes en situation de handicap; histoire et politique; justice sociale; postmodernisme; premier cycle; périodes historiques; ressource en ligne; santé; science politique; science politique et droit; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap